2
$\begingroup$

How is this approximation derived? It is from a physics book.

$C$ is a constant and for small $Cx$ we have $$1-Cx\approx \frac{1}{1+Cx}$$

Is it also true without $C$? I.e. for small $x$, $1-x\approx \frac{1}{1+x}$?

$\endgroup$
  • 2
    $\begingroup$ Notice that $(1-x)(1+x) = 1 - x^2$ and that $x^2$ is negligible. $\endgroup$ – user296602 Oct 4 '17 at 14:41
  • 2
    $\begingroup$ It should have to be true without C because you can always just have $C=1$. $\endgroup$ – Tyberius Oct 4 '17 at 14:45
5
$\begingroup$

This is because for $|t|<1$, we have $(1-t)^{-1} = 1+t+t^2+t^3+\cdots$. Then Set $t=-Cx$.

$\endgroup$
1
$\begingroup$

If you are familiar with geometric series, that is $$1+x+x^2+\cdots+x^n=\dfrac{1-x^{n+1}}{1-x}$$ and when $|x|<1$ as $n\to\infty$ this expression takes the form $$1+x+x^2+\cdots=\dfrac{1}{1-x}$$ if you set $x=Ct$ then for $|Ct|<1$ we can use this series. If $Cx$ be so small then all terms $(Ct)^n$ will be negligible and we have this approximation $$1+Ct\approx\dfrac{1}{1-Ct}$$ this approximation will be better if we use three first terms, i.e. $$1+Ct+C^2t^2\approx\dfrac{1}{1-Ct}$$

$\endgroup$
0
$\begingroup$

It is related to the geometric series. In order to derive the formula start with

$$S_n = 1+x+x^2+...+x^n$$

multiply by $x$ to obtain $$xS_n= x + x^2 +...+x^{n+1}.$$

Subtraction will result in (note that we have a lot of chancellations):

$$(1-x)S_n=1-x^{n+1} \implies S_n = \frac{1-x^{n+1}}{1-x}=1+x+x^2+...+x^{n}$$

The series converges for $|x|<1$ to give:

$1+x+x^2+... = \frac{1}{1-x}$$

Now, use $x=-Cu$ and only use the first two terms on the left-hand side to obtain your approximation.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.